2010
DOI: 10.3140/bull.geosci.1180
|View full text |Cite
|
Sign up to set email alerts
|

Contribution to knowledge on ontogenetic developmental stages of Lepidodendron mannebachense Presl, 1838

Abstract: A new reconstruction of Lepidodendron mannebachense is proposed here based on collection of well-preserved compressions from middle Moscovian volcanoclastics of the Radnice Basin, Czech Republic. These specimens that represent remains of juvenile and matured individuals make progress in our current knowledge on ontogeny of this species and help us to improve its whole plant reconstruction. The juvenile stage was characterised by an unbranched columnar stem. The mature stage of L. mannebachense had an umbrella-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 17 publications
0
14
0
Order By: Relevance
“…Efficient branch‐shedding also suggests that these plants could have spored continuously once the lowest lateral branches had reached maturity—a mode of reproduction strikingly different from that inferred for members of the Lepidodendraceae, which appear to have entered their reproductive phase only near the end of determinate growth when the crown matured (see, for example, the exceptional work by Opluštil, 2010). As in most rhizomophic lycopsids, the strobili of the Synchysidendron plant were confined to strongly anisotomous branching systems resembling that shown in Fig.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Efficient branch‐shedding also suggests that these plants could have spored continuously once the lowest lateral branches had reached maturity—a mode of reproduction strikingly different from that inferred for members of the Lepidodendraceae, which appear to have entered their reproductive phase only near the end of determinate growth when the crown matured (see, for example, the exceptional work by Opluštil, 2010). As in most rhizomophic lycopsids, the strobili of the Synchysidendron plant were confined to strongly anisotomous branching systems resembling that shown in Fig.…”
Section: Discussionmentioning
confidence: 94%
“…The lateral, strobilus‐bearing axes were derived from strongly anisotomous divisions of the main stem (which might consequently be termed “pseudomonopodial”) and were caducous (deciduous), dropping from the main stems as apical growth proceeded upward. Developmental studies of these plants strongly suggest that, in some of the more derived forms, the lateral branches were reduced to peduncles only, bearing either single or paired strobili (for discussion regarding the developmental aspects of these extinct Paleozoic lepidodendrids see Bateman and DiMichele, 1991; Bateman, 1994; Wang et al, 2003; Opluštil, 2010).…”
mentioning
confidence: 99%
“…Such deposits have permitted not only reconstruction of spatial patterns, but also reconstruction of the parent plants in remarkable detail (e.g. Oplustil 2010). The number of forests preserved in tuff is not insubstantial and occurs through much of the record, but, remarkably, there are no examples from North America.…”
Section: Discussionmentioning
confidence: 99%
“…This is clearly not the case as it has been shown that even quite large stems still retained their leaves (Thomas, ; Leary & Thomas, ). As pointed out by Boyce & DiMichele (), leaf laminae abscission left their persistent, taxonomically distinctive, leaf bases (cushions) that persisted until they were sloughed off from the largest/oldest stems by secondary growth leaving an exposed surface of periderm; see Thomas (, ), Wnuk () and Opluštil () for more details on this. It is also important to realize that the leaf cushions could move apart to some extent by the expansion of the inter‐cushion epidermis during the early stages of secondary growth (Thomas, , ) allowing the outer photosynthetic surface to remain attached to the stem even after a significant increase in girth.…”
Section: Stomatal Densitiesmentioning
confidence: 93%